Common sense in project management - Tedesco, Paul A. (Thomson Course Technology, 2006)
Common Sense in Project Management offers project managers a new way to add value, eliminate useless tasks, and empower developers. It enables you to maintain your current project management tools and processes while guiding you through the application of new steps designed to mitigate risks and raise new issues that better support your company and create competitive advantages. Learn how to bring creative problem solving to your projects, divide responsibility among team members, and solve critical problems early in a project-before they become more costly to correct. Discover the types of information gathered throughout the project and learn how that information is used to reach goals